Strategi Pengembangan Usahatani Bawang Merah Di Kabupaten Lampung Utara - Lestari, Sri Puji; Hidayat, Rizky; Sari, Yuni Elmita; Bakti, Aji Setiya; Handayani, Sri (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
Shallots are a newly grown commodity by farmers in North Lampung Regency, necessitating a study on the Shallot Farming Development Strategy in this region. This research seeks to identify the internal and external elements affecting the advancement of shallot cultivation in North Lampung Regency and to devise a strategy for its development. The respondents were determined using a census, comprising 24 farms. This research employs a survey methodology, utilising analytical tools such as IFAS, EFAS, and SWOT. This research identifies internal characteristics, with strengths including (1) the preservation of shallot harvests; (2) the land's proximity to the residence; (3) the applicability of an intercropping system; and (4) the potential for seed recultivation. The deficiencies are (1) the absence of granary or warehouse facilities for the storage of harvested crops; (2) the necessity for appropriate water and fertiliser. Identify external factors: the opportunity presented by (1) the limited production of shallots in North Lampung Regency; (2) governmental support for facilities and infrastructure; and (3) the active involvement of agricultural extension workers in promoting shallot growing. The challenges include (1) pest and disease infestations affecting shallot plants and (2) the presence of comparable items from external regions. The strategy for advancing shallot cultivation in Abung Jayo Village employs the SO strategy, which includes: (1) optimising land utilisation by acquiring information on shallot cultivation techniques from extension agents, (2) preserving harvests through the diversification of processed shallot products, and (3) enhancing communication among farmers, government, and traders to establish a local shallot market.